Synthesis, X-ray structure and antimycobacterial activity of silver complexes with alpha-hydroxycarboxylic acids - Cuin, Alexandre; Massabni, Antonio Carlos [UNESP]; Leite, Clarice Q. F.; Sato, Daisy N.; Neves, Ademir; Szpoganicz, Bruno; Silva, Marlon S.; Bortoluzzi, Adailton J. (Elsevier B.V., 2007)
In this paper, synthesis, characterization and antimycobacterial properties of a new water-soluble complex identified as silver-mandelate are described. Elemental and thermal analyses are consistent with the formula [Ag(C6H5C(OH)COO)](n). The polymeric structure was determined by single X-ray diffraction and the two-dimensional structure is based on the bis(carboxylate-O,O') dimer [Ag-O, 2.237(3), 2.222(3) angstrom]. The structure is extended along both the b and c axes through two oxygen atoms of a bidentate alpha-hydroxyl-carboxylate residue [Ag-OH(hydroxyl), 2.477(3) angstrom; Ag-O(carboxylate), 2.502(3) angstrom; O-Ag-O, 63.94(9)degrees]. A strong d(10)-d(10) interaction was observed between two silver atoms. The Ag...Ag distance is 2.8307(15) angstrom. The NMR C-13 spectrum in D2O shows that coordination of the ligand to Ag(l) occurs through the carboxylate group in solution. Potentiometric titration shows that only species with a molar metaHigand ratio of 2:2 are formed in aqueous solution. The mandelate complex and the silver-glycolate, silver-malate and silver-hydrogen-tartarate complexes were tested against three types of mycobacteria, Mycobacterium avium, Mycobacterium tuberculosis and Mycobacterium kansasii, and their minimal inhibitory concentration (MIC) values were determined. The results show that the four complexes are potential candidates for antiseptic or disinfectant drugs for discharged secretions of patients affected with tuberculosis. (c) 2006 Published by Elsevier B.V.
Keywords: silver; mycobacteria; alpha-hydroxycarboxylic acids; O-donor ligands